(untitled) (Journal of School Administration Research and Development, 2018)
Welcome to the Summer 2018 issue of the Journal of School Administration Research and Development (JSARD), our third volume. JSARD is an open-access, peer-reviewed journal that supports the development and dissemina- tion of research and scholarship in the area of K-12 school administration and leadership. Our mission is to pub- lish and disseminate relevant, high-quality literature in educational leadership in order to empower researchers, practitioners, and policy makers to improve K-12 schools. JSARD publications are possible due to the hard work of our editorial board, peer reviewers, copy editors, and authors.